Knowledge, self efficacy, and practices of barangay nutrition committee chairs on nutrition program management in Quezon Province, Philippines - Brual, Ma. Ysabel Leanne P.
Undernutrition in children under five years is still a significant health problem in the Philippines. The barangay being the most direct link to the community, has the responsibility to manage nutrition challenges, through the guidance of the BNCCs. The study aimed to determine the association of knowledge, self-efficacy, and practices (KSP) on NPM of the BNCCs in Quezon Province, Philippines. The study also determined the demographic characteristics associated with the KSP on NPM of BNCCs. Across 307 BNCCs interviewed, results showed significant weak associations between knowledge and self-efficacy (p=0, p=0.0004), knowledge and practice (p=0.1687, p=0.0030), and self-efficacy and practice (p=0.1710, p=0.0026). Results of regression analysis showed that age and educational attainment were not significantly associated with KSP on NPM. However, sex had a weak significant association with knowledge scores (rpb=-0.127, p=0.026), with females being 2.54 times more likely to have high knowledge levels compared to males. Moreover, years in service had a weak significant association with self-efficacy (p=0.059, p=0.002) and practice (p=0.132, p=0.021), indicating that longer service correlates with higher self-efficacy and practice scores. Training attendance also showed weak significant associations: nutrition training was linked to higher self-efficacy (rpb=0.127, p=0.026) and practice (rpb=-0.300, p<0.001), and nutrition program management training was linked to practice (rpb=-0.215, p<0.001). Holding other variable constant, BNCCs with nutrition training were 2.43 times more likely to have higher self-efficacy and 1,948 times more likely to have higher practice scores.